(untitled) (Journal of Chemical Engineering, 2013)
Polymeric Membrane can be produced by several methods. This paper deals computational study to prepare polymeric membrane using drying. Asymmetric and symmetric membranes can be prepared by changing the drying parameters like air flow rates, drying temperatures, and coating compositions DOI: http://dx.doi.org/10.3329/jce.v27i1.15848 Journal of Chemical Engineering, IEB Vol. ChE. 27, No. 1, June 2012: 12-20